Challenges and Opportunities of Japanese Higher Computer Science Education from the Graduates’ Perspective - Kuznetsov, Daniil (My University, 2023)
This master's thesis is a pilot study that critically examines computer science education at the university level in Japan from the perspective of the graduates. It investigates the challenges and opportunities encountered by IT graduates during their educational journey and transition to the job market. While Japan has made significant progress in integrating computer science education at the elementary level and has developed various policies to enhance the quality of higher education in general, there is a lack of specific focus on computer science education at the tertiary level. This study aims to address this research gap by examining the challenges and opportunities faced by IT graduates during their educational journey and transition to the job market, providing valuable insights for policymakers and identifying areas that require improvement in Japanese higher computer science education. The findings also offer a platform for further investigations into aspects of computer science education in Japan that demand immediate reform. The conclusions emphasize the significance of developing both hard and soft skills for successful transitions from university to the workplace. While hard skills remain important, the study underscores the growing importance of soft skills such as cognitive and analytical abilities, emotional intelligence, interpersonal skills, flexibility, resilience, professional and social skills, and strategic and opportunistic thinking skills. To facilitate this balanced development, higher education institutions should reassess and refine their curricula, incorporating real-world scenarios, collaborative learning environments, and extracurricular activities. Collaboration among educators, policymakers, and employers is essential to ensure a smooth transition for computer science graduates, foster equal opportunities, and produce professionals equipped to contribute effectively to the evolving field of technology. By addressing these challenges, graduates can maximize their potential and achieve long-term success in their careers.
Keywords: Japan, Japanese higher education, Japanese computer science education, transition to the job market